Energy-transfer-enabled photocatalytic transformations of aryl thianthrenium salts - Sun, Kai; Ge, Chang; Chen, Xiaolan; Yu, Bin; Qu, Lingbo; Yu, Bing (Nature communications, 2024)
Aryl thianthrenium salts are valuable in photocatalysis but traditionally require external electron donors for activation. This study introduces an energy transfer (EnT) strategy for the activation of aryl thianthrenium salts using 2,3,4,5,6-penta(carbazol-9-yl)benzonitrile (5CzBN) as a metal-free photocatalyst, eliminating the need for external donors. Utilizing this EnT approach, we achieve C–H deuteration of arenes under visible light with CDCl 3 as a deuterium source to synthesize various deuterated aromatic compounds, including important natural products and pharmaceuticals. Additionally, this strategy enables diverse functionalizations including borylation, arylation, cyanation, and selenylation, enhancing the applicability of aryl sulfonium salts in environmentally friendly photocatalysis. Aryl thianthrenium salts are valuable in photocatalysis but traditionally require external electron donors for activation. Herein, the authors report an energy transfer strategy for the activation of aryl thianthrenium salts, eliminating the need for external donors.